Comparative pan-genomic analysis reveals pathogenic mechanisms and genomic plasticity in Vibrio parahaemolyticus clinical and environmental isolates - Zhang, Peng; Wu, Xiaofang; Ji, Lei; Yan, Wei; Chen, Liping; Dong, Fenfen (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionVibrio parahaemolyticus is a human pathogen capable of inducing bacterial gastroenteritis. Clinical strains of V. parahaemolyticus are considered pathogenic due to their possession of hemolysin and a type III secretion system (T3SS). Some environmental isolates are also acquiring corresponding virulence genes.MethodsThis study initially examines the infection characteristics of V. parahaemolyticus, and subsequently employs pan-genomic analysis to identify genes that exhibit significant differences in distribution between environmental and clinical isolates, thereby revealing their potential impact on virulence.Results and discussionThe epidemiological analysis of clinical isolates suggests that infections of V. parahaemolyticus are more prevalent in warm seasons, with O4:KUT serotype presenting more severe symptoms. OrthoFinder analysis revealed that environmental isolates possess a higher number of core genes. PEPPAN and KEGG analysis revealed that the 10 genes exclusively found in clinical isolates were predominantly associated with virulence. Additionally, the functions of genes differentially distributed in the environment were significantly more diverse compared to those in clinical settings. Analysis of mobile genetic elements suggested that environmental isolates harbor more mobile genetic elements, implying a potential for an increased number of resistance genes. The pathogenic characteristics of the strains examined in this study, genomic diversity and variation in mobile genetic elements are highly significant for deepening our understanding of the pathogenic mechanisms of V. parahaemolyticus and for the development of strategies to prevent its infections.